2014
DOI: 10.1055/s-0034-1366973
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Predictors of Patient Satisfaction with Outcome after Cervical Laminoplasty

Abstract: Study design Prospective cohort study. Objective The purpose of the present study was to identify the predictors of patient satisfaction with outcome after cervical laminoplasty for compressive cervical myelopathy. Methods A cohort of 143 patients with compressive myelopathy who underwent cervical double-door laminoplasty between 2008 and 2011 was studied prospectively. The principal outcome was patient satisfaction with outcome at 1 year after surgery. Patient satisfaction was graded on an ordinal scale from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
(19 reference statements)
0
9
1
Order By: Relevance
“…The majority of conclusions for this review were derived from a single randomized controlled trial by Kadanka et al 25 This randomized controlled trial reported that, in patients with “milder” myelopathy (mJOA ≥ 12), (1) there was no difference in mJOA scores at 1-, 2-, 3- and 10-year follow-up between patients that received operative versus nonoperative care; (2) surgery resulted in a slower 10-m walk test than nonoperative treatment; and (3) there was no difference between treatment groups in the proportion of patients with worsened or improved clinician-based or patient reported daily activity scores (low level evidence). 25 , 26 However, no improvements in the mJOA were observed in the operative cohort of this trial, which differs from the results reported in other series of myelopathic patients undergoing surgical decompression 12 , 19 , 27 34 ; this may partially explain their finding of no difference between treatment groups. Finally, based on low level evidence, rates of hospitalization for subsequent spinal cord injury were significantly higher in patients undergoing initial conservative treatment compared to those managed operatively (HR (ref = operative treatment) = 1.57; 95% CI = 1.11-2.22, P = .011).…”
Section: Clinical Recommendationscontrasting
confidence: 99%
“…The majority of conclusions for this review were derived from a single randomized controlled trial by Kadanka et al 25 This randomized controlled trial reported that, in patients with “milder” myelopathy (mJOA ≥ 12), (1) there was no difference in mJOA scores at 1-, 2-, 3- and 10-year follow-up between patients that received operative versus nonoperative care; (2) surgery resulted in a slower 10-m walk test than nonoperative treatment; and (3) there was no difference between treatment groups in the proportion of patients with worsened or improved clinician-based or patient reported daily activity scores (low level evidence). 25 , 26 However, no improvements in the mJOA were observed in the operative cohort of this trial, which differs from the results reported in other series of myelopathic patients undergoing surgical decompression 12 , 19 , 27 34 ; this may partially explain their finding of no difference between treatment groups. Finally, based on low level evidence, rates of hospitalization for subsequent spinal cord injury were significantly higher in patients undergoing initial conservative treatment compared to those managed operatively (HR (ref = operative treatment) = 1.57; 95% CI = 1.11-2.22, P = .011).…”
Section: Clinical Recommendationscontrasting
confidence: 99%
“…17 20,22 24,28,30 34,37,39,40,44 48 The risk of bias was low or moderately low in 14 studies 17,18,22,23,28,30,31,33,34,39,44 46,48 and moderately high in 7 because of undefined or low follow-up rates. 19,20,24,32,37,40,47 A strong effect for improvement in function was observed at each time point ( P < .001): the pooled SMD across 10 studies was 1.92 (95% confidence interval [CI] = 1.41 to 2.43) at 12-months follow-up (Figure 2a) 20,22 24,28,30,32,34,45,48 ; 1.40 (95% CI = 1.12 to 1.67) across 12 studies at 13- to 36-months follow-up (Figure 2b) 17,23,30 34,37,…”
Section: Resultsmentioning
confidence: 98%
“…Thirty-two studies ultimately met the inclusion criteria and are summarized in this review. 17 48 Study characteristics are provided in Table 2 ; sample sizes ranged from 52 to 479 patients, mean ages ranged from 46 to 65 years and males comprised between 34% and 94% of the study populations. Disease pathoanatomy was also variable, with 9 studies including patients with OPLL (range = 6.6% to 33.6% of patients); of the remaining studies, 12 specifically excluded OPLL patients and 6 did not specify whether or not OPLL patients were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-six studies [20,2224,27,28,34,35,38,39,42,45,47,48,56,57,6062,65,66,6971,73,74,79,81,82,84–86,88,90,91,116] containing 129 patients with CSF of 5007 patients after cervical surgery were included. Figure 15 shows that the incidence was 1.9% (95% CI 1.3%–2.4%), with substantial heterogeneity of incidence observed.…”
Section: Resultsmentioning
confidence: 99%